Enhanced visible light photodegradation activity of RhB/MB from aqueous solution using nanosized novel Fe-Cd co-modified ZnO - D., Neena; Kondamareddy, Kiran Kumar; Bin, Han; Lu, Dingze; Kumar, Pravin; Dwivedi, R. K.; Pelenovich, Vasiliy O.; Zhao, Xing-Zhong; Gao, Wei; Fu, Dejun (Scientific reports, 2018)
A series of novel Fe-Cd co-doped ZnO nanoparticle based photocatalysts are successfully synthesized by sol-gel route and characterized using scanning electron microscopy (SEM), energy dispersive X-ray emission (EDX), transmission electron microscopy (TEM), X-ray diffraction (XRD), UV-Vis spectroscopy, X-ray photoelectron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) techniques. The photocatalytic activity of ZnO nanoparticles doped with various atomic weight fraction of Fe and Cd has been investigated under visible light irradiation using the Methylene Blue and Rhodamine B dye in aqueous solution. The FeCd (2%):ZnO (ZFC-1) exhibit the highest photocatalytic activity in terms of rate constant as K MB = 0.01153 min −1 and K RhB = 0.00916 min −1 ). Further, the re-usability of the ZFC-1 photocatalyst is studied which confirms that it can be reused up to five times with nearly negligible loss of the photocatalytic efficiency. Moreover, the role of photoactive species investigated using a radical scavenger technique. The present investigations show that the doping concentration plays significant role in photocatalytic performance. The visible light absorption shown by Fe-Cd co-doped ZnO nanoparticles is much higher than that of undoped body probably due to co-doping, and the charge carrier recombination is decreased effectively which yields a higher photocatalytic performance. The mechanism for the enhancement of photocatalytic activity under visible light irradiation is also proposed.